Study of COVID-19 Health Protocol Standards in Construction Industry of Indonesia - Ratih Dewi Shima; Iris Mahani; Krishna Suryanto Pribadi; Kevin Andika Hartono (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
Due to the increase in GNI per capita, the Indonesian government has launched its national economic recovery program in response to the COVID-19 emergency crisis, known as the New Normal and ordered to partially resume on-hold infrastructure projects followed by the implementation of a new, integrated COVID-19 health protocol. This research presents a study of health protocol standard implementation in the construction industry with the aim of formulating recommendations for minimum criteria elements that can be used for construction services companies at all levels. The domain-taxonomy analysis approach was used as the research method: the ISO/PAS 45005:2020 and ILO standards were adapted to Ministerial Regulation of PUPR No. 10 Year 2020. A gap analysis was conducted with Singapore, Malaysia, and Australia. The analysis generated four segregated main groups of elements with level-2 sub criteria. The main groups of elements were: Planning, Prevention, Handling, and Control and Evaluation. These criteria were validated and implemented in a case study of state-owned construction enterprises, here called PT. X and PT. Y, with large, qualified construction companies. From the implementation analysis it was found that PT. X and PT. Y had implemented the minimum criteria of the COVID-19 health protocol for construction workers very well.